FINANCING OF BRAZILIAN COMPANIES IN THE LIGHT OF PECKING ORDER AND MARKET TIMING THEORIES: EVIDENCE FROM REGIONALITY - Iglesias, Thayla Machado Guimarães; Guimarães, Thayse Machado; Pereira, Vinícius Silva; Penedo, Antônio Sérgio Torres (Advances in Scientific and Applied Accounting, 2021)
Goals: This paper aims to understand how macroeconomic factors and firms’ characteristics impact the definition of the Brazilian companies’ capital structure in the regional context. Method: The study involved 426 non-financial Brazilian companies listed on B3 during the period from 2007 to 2017. In the internal perspective, the variables liquidity, ROE, tangibility and size were used, while, in the external approach, the variables GDP, inflation and periods of crisis, concerning the years 2008 and 2015. Results: The results reveled that the majority of organizations are located in the southeastern and southern regions (86%), with control by the regions being an important factor in decision making regarding the financing of companies. Also, the Pecking Order theory was corroborated, with respect to the characteristics of firms, since companies tend to prioritize the use of internal resources over third resources, especially during economic recession, when there is a greater impact on corporate profits. However, the Market Timing theory has not been ratified, which suggests that companies do not tend to observe the windows of opportunity for the issue of securities. Contributions: It is relevant to investigate how companies’ financing decisions are impacted by issues that go beyond the firms’ characteristics, in other words, how they are influenced by the environment in which they operate, especially with regard to macroeconomic factors and the regional context. Thus, this research advances in the literature not only because it covers external factors, but also because it considers the regional differences in Brazil.